(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Breast cancer remains the most prevalent malignancy among women globally, with endocrine therapy representing the cornerstone of treatment for hormone receptor-positive subtypes. However, the emergence of therapeutic resistance poses significant clinical challenges. This narrative review presents a comprehensive computational framework integrating mathematical modeling, systems biology, and clinical pharmacology to understand hormonal dynamics in breast cancer progression and treatment response.